Clinical impact of posterior wall isolation in catheter ablation for persistent atrial fibrillation: A systematic review and meta‐analysis. Issue 10 (20th September 2022) - Liu, Xiaohua; Gao, Xiaofei; Chen, Lian; Shen, Lishui; Liu, Meijun; Xu, Yizhou
Abstract: Background: The clinical outcomes of pulmonary venous isolation alone for persistent atrial fibrillation (PerAF) remain unclear. Adjuvant posterior wall isolation (PWI) has become a potential supplementary strategy for improving the outcome of PerAF ablation. This meta‐analysis aimed to evaluate the effect of PWI added to catheter ablation for PerAF. Methods: PubMed, EMBASE, and Cochrane Library databases were searched for studies comparing the outcomes of PerAF ablation with and without PWI. The efficacy outcomes were recurrence of atrial arrhythmia (AA), atrial fibrillation (AF), and atrial tachycardia (AT), and the safety outcome was adverse events. Results: In total, eight studies with 1428 patients were included in the pooled analyses. The results showed that PWI significantly reduced the recurrence of AA (RR = 0.69, 95% CI = 0.55–0.87, p = .002, I 2 = 63%) and AF (RR = 0.57, 95% CI = 0.40–0.80, p = .001, I 2 = 70%). AT recurrence (RR = 0.92, 95% CI = 0.67–1.27, p = .63, I 2 = 42%) and adverse events (RR = 1.11, 95% CI = 0.67–1.84, p = .70, I 2 = 0%) were comparable between the two groups. In the sub‐analyses, the efficacy of PWI in reducing AA recurrence was consistent in patients who underwent cryoablation or debulking ablation. Conclusion: PWI effectively decreased AA recurrence after PerAF ablation without increasing the risk of AT or procedure‐related complications. However, more randomized studies are needed to confirm these results.